(3faK Gdbde aj TQM dGejg GdYLes - (3GdMSjf Hf Ydj Hf eMeO Hf YHO GdUeO, CHh ESeGYjd, eDjO GdOjf, GdCUHgGfj GdWZQGFj,J (B513 (3g` s
(3ChdgG (B:s
(3OY GdhTGI heG bGdhG heGfbdhG Hjfi hHjfce eGdjS jfaUd dce SQGFQ ai bdHi eNHCI dG GdcJH JfaYfi ajgG hdG GdQSd s
(3BNQgG (B:s
(3ce MSfJ dPI ddeQA bGJdI ef MjK de jOQ Cf GdSe ai GdQSe hdjcf gPG BNQ GdeTQhM hGdTQM , aGdMeO ddg s
(3HgG VHW HGdTcd cKjQs
(3GdeNWhW eQbe GdUaMGJs
(3cJHJ HYV YHGQGJgG HGdUaQI hGdNVQI hGdMeQI s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3GdfSNI HgG JdhjK s
Keywords: (3GdCOHs